Effect of millings among broiler breeder parent groups of different body weight on broiler performance: 11. commercial broiler performance - Süleyman Dere; M.Ali Tekeş (Eurasian Journal of Veterinary Sciences)
The purpose ol (his study is to determine the effects of housing together male and female broiler parents with different body weight at 22 weeks old age during production period on progeny performance. As the research material. 778 Avian female and 116 Peterson male broiler breeders, and totally 459 chicks obtained from that broiler breeders were used. Parent male and female chickens were separately divided into three base body weight groups called low, middle and high at 22 weeks old age . Separately three body weight subgroups which have almost similar variance and average values were obtained from base body weight groups by using sensitive sampling method. Six male and 64 female broiler breeder parent chickens obtained from bodyweight subgroups were housed in 9 pens during production period, feed conversion, body weight and performance indices of progeny groups were determined. Performance indices for 49 days old progenies of Hh (Light male x light female), Ha. Ho, Ah. Aa (Heavy male x heavy female), Ao. Oh. Oa and Oo (Middle male x middle female) parent groups were estimated as 193.71, 181.54, 226.83, 211.40, 204.44, 188.23, 203.40, 201.14 and 202.40, respectively. As a result , it can be said that Body weight of Broiler breeders can influence Body weight of their own progenies. When average progeny (commercial broilers) bodyweights and performance index values were taken into consideration, it may be possible to say ıha! if light males and females with middle bodyweights at sexual maturity age are used in broiler breeder pareni matings, optimum performance in progenies of Broiler breeders will be able to be obtained.